Monodominant natural vegetation provides models for nature-based cereal production. (March 2022) - Lenné, J; Wood, D
Nature-based solutions, principally diverse systems, are increasingly being promoted as the solution to future food production as they are perceived to be more productive, resilient and ecologically based. This 'paradigm of in-field diversity' approach is inciting a growing perception that monocultures, the source of most global food production, are ecologically dysfunctional and highly vulnerable to diseases and pests. Our perspective paper clearly shows that natural monodominant vegetation is common in nature and that the ancestral species of major cereals including wheat, barley and rice grew in monocultures maintained by disturbances such as fire or flood. Early farmers mimicked these ecological stresses during field management, favouring annual monodominant crops. We also present well-supported evidence that cereal monocultures are an ancient method of farming founded in the origins of agriculture and that modern plant breeding generates and supports monoculture crops that are inherently genetically diverse and usually resistant to prevailing diseases and pests. Until research has been done on the ecology, agronomy and management of diverse nature-based solutions to future agriculture, the scarce funding to agricultural research for future food production is better targeted at improving monoculture agriculture to be more efficient, productive, resilient and environmentally benign. Monoculture agriculture, particularly for cereals, is a proven natural model for future food production.